Doctor, can we prevent food allergy and eczema in our baby?. Issue 3 (June 2016) - Waserman, Susan
Abstract : Purpose of review: The purpose is to review evidence from recent clinical trials that focus on early life interventions to prevent the onset of eczema and food allergy. Recent findings: There is evidence that skin barrier defects may be a risk factor for the development of eczema and may increase the risk of early onset food sensitization and allergy. The measurement of transepidermal water loss as a marker of skin barrier defect may be a simple, noninvasive measurement that may predict who is at risk of eczema, however, the protective effects of daily moisturizer application in high-risk infants remains unclear. Although there is increased attention on the role of intestinal microbiota and its influence on sensitization, there is limited evidence to support the preventive effects of probiotics on allergic diseases. Recent clinical trials have provided much needed evidence supporting the early introduction of peanut in the primary and secondary prevention of peanut allergy in high-risk children. There still remain unanswered questions and challenges regarding protocols and implementation of current recommendations. Summary: Although progress has been considerable, the fact is that there are no simple strategies to prevent the development of eczema and food allergy in infants. Physicians must remain informed of the dynamic evidence in allergy prevention to make responsible, informed recommendations to families.